Integrated transcriptomic and metabolomic analyses revealed the molecular mechanism of terpenoid formation for salicylic acid resistance in Pulsatilla chinensis callus - Dong, Yanjing; Qin, Qian; Zhong, Guoyue; Mu, Zejing; Cai, Yating; Wang, Xiaoyun; Xie, Huan; Zhang, Shouwen (Frontiers in Plant Science, 2023)
As a kind of traditional Chinese medicine, Pulsatilla chinensis (Bunge) Regel is well known for its anti-inflammation and anti-cancer activity, which is attributed to its active components including total saponins and monomers. Although P. chinensis is widely applied in clinical and veterinary treatment, its commodity medicinal materials is usually adulterated. To clarify the synthesis and metabolism mechanisms of class components in callus terpenes of P. chinensis, a certain concentration of salicylic acid (SA) hormone elicitor is added to the callus before being analysed by transcriptomic and metabolomic techniques. Results show that the content of Pulsatilla saponin B4 in the callus suspension culture is significantly increased up to 1.99% with the addition of SA. Kyoto Encyclopedia of Genes and Genomes(KEGG) enrichment analysis showed that the differentially expressed genes were mainly enriched in 122 metabolic pathways, such as terpenoid metabolism-related pathways: terpenoid skeleton synthesis pathway, monoterpenoid biosynthesis pathways, diterpenoid biosynthesis pathways, and ubiquinone and other terpenoid-quinone biosynthesis pathways. A total of 31 differentially accumulated metabolites were obtained from four differential groups. Amongst 21 kinds of known chemical components in P. chinensis, deoxyloganic acid is the only monoterpenoid; the others are triterpenoids. In summary, this study found that SA elicitors can affect the metabolic changes of terpenoids in P. chinensis callus, which provided a basis for analysing the genetic regulation of terpenoid components of leucons.